Scalable Multisubject Vital Sign Monitoring With mmWave FMCW Radar and FPGA Prototyping - Benny, Jewel; Moudhgalya, Narahari N.; Khan, Mujeev; Kumar Meena, Hemant; Wajid, Mohd; Srivastava, Abhishek (IEEE sensors journal, 2025)
In this work, we introduce an innovative approach to estimate the vital signs of multiple human subjects simultaneously in a noncontact way using a frequency-modulated continuous-wave (FMCW) radar-based system. Traditional vital sign monitoring methods often face significant limitations, including subject discomfort with wearable devices, challenges in calibration, and the risk of infection transmission through contact measurement devices. To address these issues, this research is motivated by the need for versatile, noncontact vital monitoring solutions applicable in various critical scenarios. This work also explores the challenges of extending this capability to an arbitrary number of subjects, including hardware and theoretical limitations. Supported by rigorous experimental results and discussions, the article illustrates the system's potential to redefine vital sign monitoring. A field-programmable gate array (FPGA)-based implementation is also presented as proof of concept for a hardware-based and portable solution, improving upon previous works by offering 2.7× faster execution and 18.4% less look-up table (LUT) utilization, as well as providing over 7400× acceleration compared to its software counterpart.